INVESTIGATION OF THE SOLUTION PROCESS OF THE PROBLEMS POSED BY SECONDARY SCHOOL STUDENTS IN PISA TYPE - BEDİR, Sümeyye Güner and BAL , Ayten Pınar (SSD Journal, 2024)
In the 21st century, which is the dynamic information age, the inevitability of change,it is important for students to be prepared for PISA questions by increasing their mathematical literacy. The aims of mathematics teaching programs are to be able to overcome the problems encountered in real life, to be able to see the relationships between events and to produce original solutions. Studies show that there is a relationship between the acquisition of mathematical concepts and the problem solving process (Yılmaz & Yenilmez, 2008). Question types within the scope of PISA aim to measure skills such as creative thinking, reading-interpreting-evaluation of the given information, problem-solving-resulting (Savran, 2004). With mathematics education, students will develop their problem-solving skills and overcome them. These reasons bring students’ problem posing skills to the fore. This research was conducted to examine the solution process of the problems posed by secondary school students in the PISA type. The study group consists of 43 sixth grade students in Dörtyol district of Hatay province in the 2018-2019 academic year. The research, Cresswell, 2007; Yıldırım & Şimşek, 2011) working group was determined. One of the most successful schools in the region and one of the best classrooms was chosen as the benchmark. In the research, they were asked to pose three problems in accordance with the nature of PISA as a data collection tool, and the solutions of the problems they posed were evaluated within the framework of data analysis. As a result of the research, students are expected to be aware of real life problems and to be able to create such problems. Students are expected to use different strategies and develop different perspectives in problem solving. In addition, the students participating in the research are expected to make meaningful learning with their active participation by establishing a connection between daily life and mathematics lesson. Thus, they are expected to be aware that the mathematics course is not only a course but also necessary throughout their lives.